Book review: Beyond 18 - Leaving child care institutions: a study of aftercare practices in five states of India. UNICEF: India Country Office - Kenny McGhee (Scottish Journal of Residential Child Care)
This is a review of an overview report of a study conducted by Udayan Care in India with support from the United Nations Children's Fund (UNICEF), Tata Trusts and the five State Governments of Delhi, Gujarat, Karnataka, Maharashtra and Rajasthan.